Hypertensive Erkrankungen in der Schwangerschaft - Schneider, Johanna; Walz, Gerd; Neumann-Haefelin, Elke (DMW - Deutsche Medizinische Wochenschrift, 2021)
Hypertensive disorders occur in up to 10 % of pregnancies and increase both maternal and fetal morbidity and mortality. The most important differential diagnoses comprise pre-existing chronic hypertension, pregnancy-associated hypertension, and preeclampsia with simultaneous proteinuria. Antihypertensive therapy during pregnancy should be initiated when blood pressure is 150–160/100–110 mmHg. With regard to an earlier initiation of therapy, the data situation is not clear. Pre-eclampsia is defined as new or pre-existing elevated blood pressure ≥ 140/90 mmHg in pregnancy with at least one new organ manifestation, usually proteinuria ≥ 300 mg/day or ≥ 30 mg/mmol in the protein-creatinine ratio. Thrombotic microangiopathies TTP and aHUS are altogether rare but potentially life-threatening diseases that should be clarified in case of severe or atypical courses.
Keywords: Hypertonie; Schwangerschaft; Präeklampsie; thrombotische Mikroangiopathie